Die Frau in Sparta im Vergleich mit der Frau im Dritten Reich - Nina Höflinger (Historia.scribere)
The Spartan women in comparison with the women during the NS-regime. The following proseminar-paper is about the comparison between the life of women in ancient Sparta and the women in Germany of Second World War. It will examine the similarities and differences of these women. As will be shown, there were several analogies in the topics we are discussing in the following proseminar-paper.